The 2019 WACEM Expert Document on Hybrid Simulation for Transforming Health-care Simulation Through “Mixing and Matching” - Lateef, Fatimah (J Emerg Trauma Shock, 2019)
With the multitude of options available under the umbrella of “simulation” today, we have a larger repertoire of choices in our educational journey and outreach. These provide a platform for us to really transform health-care simulation from the traditional, unimodality simulation, to more complex, high fidelity, integrated, and engaging multimodality techniques. The main thrust must be to enhance clinical decision-making in patient care, to solve real-world clinical problems. Hybrid simulation (HS) utilizes at least two different simulation modalities, whereby combining them will enable one type of simulation modality to enhance the other, with the proper alignment, coordination, and interfacing between the modalities. Although the term is often used interchangeably, HS is slightly different from multimodality simulation. The latter refers to the use of multiple types of simulation in the same scenario or place. The main objectives for using HS have to be as follows: (1) for the acquisition of knowledge and skills by the best combination of methodologies, (2) for clinical performance improvement at all levels of care through the creation of as close as possible to real-world situation and problems, (3) to be able to sustain motivation and passion of our spectrum learners in their educational continuum, and (4) to provide a rich, exciting, and stimulating learning platform and environment, which can trigger deep learning and understanding. This article will also share some examples and cases utilizing HS in transforming health-care simulation.